SKRINING FITOKIMIA DAN UJI TOKSISITAS DARI EKSTRAK DAUN MAHANG (Macaranga bancana) - Rianti Putri; Rudi Hendra Sy; Hilwan Yuda Teruna (LPPM Universitas Muhammadiyah Riau, 2019)
Macaranga bancana (Euphorbiaceae) known as “mahang” which is wide spread in Indragiri Hulu, Riau Province and also believed to has medicinal properties. This study to evaluate the secondary metabolites contents and toxicity activity from various extracts of M. bancana leaves. Extraction process were done by using maceration method with various solvents, such as n-hexane, dichloromethane, ethyl acetate, methanol, and ethanol. Toxicity analysis was done by Brine Shrimp Lethality Test (BSLT). The results of phytochemical screening showed that M. bancana leaves contain terpenoid, steroid, flavonoid and phenolic. Toxicity analysis showed that n-hexane extracts prossessed the highest level of toxicity followed by dichloromethane, ethyl acetate and methanol extracts with LC50 value of 65; 87; 227; 605 μg/mL, respectively while ethanol extract has not toxic. Therefore, it could be concluded that M. bancana has good toxicity level and could be used as screening for anticancer.